2013
DOI: 10.1103/physrevlett.110.205505
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Mapping of Icosahedral Short-Range Order in a Melt-SpunZr36Cu64Metallic Glass

Abstract: By analyzing the angular correlations in scanning electron nanodiffraction patterns from a melt-spun Zr(36)Cu(64) glass, the dominant local order was identified as icosahedral clusters. Mapping the extent of this icosahedral short-range order demonstrates that the medium-range order in this material is consistent with a face-sharing or interpenetrating configuration. These conclusions support results from atomistic modeling and a structural basis for the glass formability of this system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 27 publications
3
70
0
1
Order By: Relevance
“…We can see that the network mainly consists of bicap sharing connection and this type of connection should be a key to understand the medium-range order in metallic glasses. It is consistent with the recent experimental observation [12] by the scanning electron nanodiffraction that suggests a face sharing or bicap sharing model of the icosahedral medium-range order in a Zr36Cu64 glass. …”
Section: Geometrical Feature Of Icosahedral Networksupporting
confidence: 92%
See 1 more Smart Citation
“…We can see that the network mainly consists of bicap sharing connection and this type of connection should be a key to understand the medium-range order in metallic glasses. It is consistent with the recent experimental observation [12] by the scanning electron nanodiffraction that suggests a face sharing or bicap sharing model of the icosahedral medium-range order in a Zr36Cu64 glass. …”
Section: Geometrical Feature Of Icosahedral Networksupporting
confidence: 92%
“…The early works of computer simulation have shown that the icosahedral order would exist in both liquid and glassy phases [3,4]. After the discovery of good metallic glass-formers [5,6], experimental observations [7][8][9][10][11][12] has reported that the icosahedral short-range order does exist in metallic glasses and that some medium-range order may also exist beyond the icosahedral short-range order. However, it was little known how the icosahedral short-range order is arranged and extended to form a medium-range order in glassy phases.…”
Section: Introductionmentioning
confidence: 99%
“…Many types of building blocks in the amorphous structure of different BMGs have been found from experimental structural characterization (e.g. X-ray diffraction or neutron scattering) [184][185][186] and molecular simulations [16,182]. For example, icosahedra cluster, which has a high packing efficient or density comparable with face centered cubic (fcc) or hexagonal close-packed (hcp) structure but is not accepted in crystalline symmetry, usually prevails in some BMGs [182,187], while the main local SRO unit is the tri-capped trigonal prism for some Fe-based or Ni-based metallic glasses [16,188] (e.g.…”
Section: Composition and Structurementioning
confidence: 99%
“…11 Indeed, such local order in MGs/liquids has been extensively documented in the past couple of decades in numerous experimental studies using X-ray/neutron scattering and nanobeam electron diffraction, 12,39,[91][92][93] as well as computer simulations employing ab initio or empirical interatomic interaction potentials. 10, 25, 30-32, 52, 63-69, 94, 95 However, there has also been recent claims of hidden crystal-like topological order in MGs 36-39, 96, 97 in addition to colloidal disordered materials.…”
Section: Introductionmentioning
confidence: 99%